A Comparative Study of the Evolution of Iranian e-Business Models with the Most Successful Global Business Models - Emad Farazmand; Reza AliBakhshi (Journal of Information Technology Management)
Nowadays portions of the national income in developed countries are due to income of the electronic businesses and electronic commerce. Realizing these businesses and their strategical governance priorities regarding the development of those business with most profitability are among the most important necessities in this field. Accordingly, indicating the status quo of electronic business in our country can be of great value in having an effective policy-making. In this research we aim to compare the status of Iranian electronic commerce with the most successful ones in the globe. To do so, first we have considered the top hundred website according to Alexa ranking, nationally and globally, and we have extracted their main business models as well. Afterward, the frequency of these business models in addition to the average ranking of their websites have been extracted and compared accordingly. Results of this study show that those electronic business models which are highly valued globally are less attractive for Iran’s electronic commerce.